Assessing Bioavailability and Bioactivity of 4-Hydroxythiazolidine-2-Thiones, Newly Discovered Glucosinolate Degradation Products Formed During Domestic Boiling of Cabbage - Hoffmann, Holger; Ott, Christiane; Raupbach, Jana; Andernach, Lars; Renz, Matthias; Grune, Tilman; Hanschen, Franziska S. (Frontiers in Nutrition, 2022)
Glucosinolates are plant secondary metabolites in cruciferous vegetables (Brassicaceae) that are valued for their health beneficial potential. Frequently consumed representatives of these vegetables for example are white or red cabbage, which are typically boiled before consumption. Recently, 3-alk(en)yl-4-hydroxythiazolidine-2-thiones were identified as a class of thermal glucosinolate degradation products that are formed during boiling of cabbage. Since, these newly discovered compounds are frequently consumed, which raises questions on their potential uptake as well as their possible bioactive functions. Therefore, 3-allyl-4-hydroxythiazolidine-2-thione (allyl HTT) and 4-hydroxy-3-(4-(methylsulfinyl)butyl)thiazolidine-2-thione (4-MSOB HTT) as degradation products of the respective glucosinolates sinigrin and glucoraphanin, were investigated. After consumption of boiled red cabbage broth, recoveries of consumed amounts of the degradation products in 24 h collective urine were 18 ± 5% for allyl HTT and 21 ± 4% for 4-MSOB HTT (mean ± SD, n=3). To investigate the stability of the degradation products during uptake and to elucidate the uptake mechanism, both an in vitro stomach and an in vitro intestinal model were applied. The results indicate that the uptake of allyl HTT and 4-MSOB HTT occurs by passive diffusion. Both compounds show no acute cell toxicity, no antioxidant potential, and no change in NAD(P)H dehydrogenase quinone 1 (NQO1) activity up to 100 µM. However, an inhibition of glycogen synthase kinases-3 (GSK-3) in the range of 20% for allyl HTT for the isoform GSK-3β and 29% for 4-MSOB HTT for the isoform GSK-3α at a concentration of 100 µM was found. Neither health-promoting nor toxic effects of 3-alk(en)yl-4-hydroxythiazolidine-2-thiones were found in the four tested assays carried out in this study, which is in contrast to the properties of other glucosinolate degradation products such as isothiocyanates.